Prevention of Activities of Misusing the Mind in Religion - Arsyad, Nasrullah; Harianto, Asis; Ukas Marzuk, Abdul; Zulfadli,; Djanggih, Hardianto (International Journal of Psychosocial Rehabilitation, 2020)
Terrorists are not ordinary forms of destructive violence but crimes that can damage world peace and human security (crimes against the peace and security of mankind). One of the countries that produces many terrorism offenders is Indonesia. The majority of Indonesia's population is Muslim and is used by a group of people by spreading misguided and misleading religious understandings to undermine the Islamic faith among Muslims in Indonesia. One of the main causes of terrorism is a wrong understanding of the teachings of Islam. Therefore, a deradicalization approach is needed aimed at sympathizers, supporters, and militants both in the midst of the community and in penitentiaries who are serving sentences. The purpose of deradicalization is to turn off the source of terrorism's fire, namely a radical religious understanding that is incompatible with the purity of the teachings of Islam itself.